Clinical Reasoning Assessment Methods: A Scoping Review and Practical Guidance. (June 2019) - Daniel, Michelle; Rencic, Joseph; Durning, Steven J.; Holmboe, Eric; Santen, Sally A.; Lang, Valerie; Ratcliffe, Temple; Gordon, David; Heist, Brian; Lubarsky, Stuart; Estrada, Carlos A.; Ballard, Tiffany; et al.
Abstract : Purpose: An evidence-based approach to assessment is critical for ensuring the development of clinical reasoning (CR) competence. The wide array of CR assessment methods creates challenges for selecting assessments fit for the purpose; thus, a synthesis of the current evidence is needed to guide practice. A scoping review was performed to explore the existing menu of CR assessments. Method: Multiple databases were searched from their inception to 2016 following PRISMA guidelines. Articles of all study design types were included if they studied a CR assessment method. The articles were sorted by assessment methods and reviewed by pairs of authors. Extracted data were used to construct descriptive appendixes, summarizing each method, including common stimuli, response formats, scoring, typical uses, validity considerations, feasibility issues, advantages, and disadvantages. Results: A total of 377 articles were included in the final synthesis. The articles broadly fell into three categories: non-workplace-based assessments (e.g., multiple-choice questions, extended matching questions, key feature examinations, script concordance tests); assessments in simulated clinical environments (objective structured clinical examinations and technology-enhanced simulation); and workplace-based assessments (e.g., direct observations, global assessments, oral case presentations, written notes). Validity considerations, feasibility issues, advantages, and disadvantages differed by method. Conclusions: There are numerous assessment methods that align with different components of the complex construct of CR. Ensuring competency requires the development of programs of assessment that address all components of CR. Such programs are ideally constructed of complementary assessment methods to account for each method's validity and feasibility issues, advantages, and disadvantages. Abstract : Supplemental Digital Content is available in the text.